2014
DOI: 10.7150/ijms.8854
|View full text |Cite
|
Sign up to set email alerts
|

Screening Tests Using Serum Tissue Transglutaminase IgA May Facilitate the Identification of Undiagnosed Celiac Disease among Japanese Population

Abstract: The prevalence of celiac disease (CD) among Japanese population has been unknown, whereas it has been increasingly recognized in the US and in the European countries. The aim of the present study is to identify possible cases with CD among Japanese population and clarify the relevance of screening for the disease.We conducted a serologic screening for the disease among 710 Japanese patients and 239 healthy volunteers at a local tertiary teaching hospital, using an anti-tissue transglutaminase IgA (TTG-IgA) tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Using samples from pregnant women randomly selected from the population is a strength and minimize the risk of selection bias. Using radiobinding assays to assess tTG autoantibodies with proven high diagnostic sensitivity and specificity for celiac disease [8,12,34,35]. Moreover, radioligand binding assays have been used in several previous prospective screening studies for celiac disease [8,35] and proven the best performance as compared to other ELISAs in an international tTG workshop [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using samples from pregnant women randomly selected from the population is a strength and minimize the risk of selection bias. Using radiobinding assays to assess tTG autoantibodies with proven high diagnostic sensitivity and specificity for celiac disease [8,12,34,35]. Moreover, radioligand binding assays have been used in several previous prospective screening studies for celiac disease [8,35] and proven the best performance as compared to other ELISAs in an international tTG workshop [36].…”
Section: Discussionmentioning
confidence: 99%
“…Serum samples were kept at −20°C freezer and shipped to Clinical Research Center (CRC) at Lund University in Malmö, Sweden, for analysis of IgA-tTG and IgG-tTG in separate assays as previously described [10,12]. In short, 35 S labelled tTG were produced by coupled transcription/translation system using the TNT® Coupled Reticulocyte Lysate an in vitro single-tube system in the laboratory.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study from eastern country was conducted on 225 dyspeptic Iranian patients, revealing that about 6% of the selected patients with functional dyspepsia had occult celiac disease (Keshavarz et al, 2010). Also, Nakazawa et al (2014) found that seven of the eleven patients with anti-tTG exhibited villous atrophy and partial infiltration of intraepithelial lymphocyte. On the other hand, Rostami et al (1999) showed that 3 out of 1000 patients had partial villous atrophy with anti-tTG results and was defined as occult celiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…With the advent of multiple serological tests for CD, a substantial number of previously undiagnosed cases have been identified, yielding a prevalence of approximately 1% among the Caucasian population in the US and Europe [1,2]. Nakazawa et al [3] used serological tests based on tissue transglutaminase-IgA (TTG-IgA) and histological examination to identify CD among the Japanese population. Their screening program among 710 patients identified seven cases (0.98%) with both positive TTG-IgA and the pertinent mucosal changes, compatible with celiac disease, which study would shed light firstly on the discussion of possible diagnosis of celiac disease among East Asian population.…”
Section: Introductionmentioning
confidence: 99%